Manajemen kompetensi dosen Universitas Muhammadiyah Jakarta - Saepudin, Saepudin; Fattah, Nanang; Tanjung, Hendri; Alim, Akhmad (Ta'dibuna: Jurnal Pendidikan Islam, 2019)
The purpose of this research is to study and analyze the competency management of Universitas Muhammadiyah Jakarta lecturers. The theoretical approach used is the theory of lecturer competency management which refers to policies, programs, and techniques for implementing scientific competence, propagation competence, moral competence, and creed competence. This research method uses qualitative research methods by describing and analyzing the reality that occurs in the object under study which refers to the naturalistic paradigm by constructing the reality of research naturally. The findings show that the competence management of lecturers at the University of Muhammadiyah Jakarta is considered very effective by integrating academic and spiritual characters. The competency management of the Muhammadiyah University of Jakarta lecturers was analyzed through 4 aspects, namely the management of scientific competencies, the management of da'wah competencies, the management of moral competencies and the management of aqidah competencies. Success in managing the competencies of lecturers at the Universitas Muhammadiyah Jakarta is increasing the integration of academic character and spiritual character of lecturers in the realm of theory and implementation. Abstrak Tujuan penelitian ini adalah untuk mengkaji dan menganalisis manajemen kompetensi dosen Universitas Muhammadiyah Jakarta. Pendekatan teori yang digunakan yaitu teori manajemen kompetensi dosen yang mengacu pada kebijakan, program dan teknik pelaksanaan kompetensi keilmuan, kompetensi dakwah, kompetensi akhlak dan kompetensi akidah. Metode penelitian ini menggunakan metode penelitian kualitatif yaitu dengan cara menggambarkan dan menganalisis tentang realitas yang terjadi pada objek yang diteliti yang mengacu pada paradigma naturalistis dengan cara mengonstruksi realitas penelitian secara alamiah. Hasil temuan penelitian menunjukkan bahwa manajemen kompetensi dosen Universitas Muhammadiyah Jakarta dinilai sangat efektif dengan mengintegrasikan karakter akademik dan karakter spiritual. Manajemen kompetensi dosen Universitas Muhammadiyah Jakarta dianalisis melalui 4 aspek yaitu pengelolaan kompetensi keilmuan, pengelolaan kompetensi dakwah, pengelolaan kompetensi akhlak dan pengelolaan kompetensi aqidah. Keberhasilan dalam pengelolaan kompetensi dosen Universitas Muhammadiyah Jakarta yaitu meningkatnya integrasi karakter akademik dan karakter spiritual dosen dalam ranah teori dan implementasi.